43.9k views
0 votes
Solve the system of equations below. You may want to use the method by substitution starting with the second equation.

Solve the system of equations below. You may want to use the method by substitution-example-1
User Zxcat
by
5.9k points

1 Answer

3 votes

Given

The system of equation,


\begin{gathered} 3x-2y=42 \\ 5x+10y=-10 \end{gathered}

To find:

The solution to the system of equation.

Step-by-step explanation:

It is given that,


\begin{gathered} 3x-2y=42 \\ 5x+10y=-10 \end{gathered}

That implies,

From the second equation,


\begin{gathered} 5x+10y=-10 \\ /5\Rightarrow x+2y=-2 \\ \Rightarrow x=-2y-2 \end{gathered}

Substitute x in the first equaton,


\begin{gathered} 3(-2-2y)-2y=42 \\ -6-6y-2y=42 \\ -8y=42+6 \\ -8y=48 \\ y=(48)/(-8) \\ y=-6 \end{gathered}

Therefore,


\begin{gathered} x=-2(-6)-2 \\ x=12-2 \\ x=10 \end{gathered}

Hence, the solution is (10,-6).

User Prissy
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.